A Corpus-Based Readability Formula for Estimate of Arabic Texts Reading Difficulty - Mat Daud, Nuraihan; Hassan, Haslina; Abdul Aziz, Normaziah (IDOSI Publication, 2013)
The present study is aimed at designing a formula for estimating the difficulty of reading Arabic texts. Flesch, Gunning Fox and Dale-Chall are some of the formulae that have been used for measuring English texts difficulty. Some of them have been automated making it easy for users to check the readability level of a particular text. A few scholars have attempted to come up with a readability formula for Arabic, but none has been automated. This study is thus conducted to find the formula that would make it possible for users to measure the difficulty level of Arabic texts online. This will greatly help in materials selection for reading comprehension and testing. This paper will present the prototype of a readability formula which is based on a corpus for estimating the difficulty of Arabic written documents.